Metal catalyzed cross-coupling reactions and more. - Meijere, A. de; Bräse, Stefan; Oestreich, Martin (Wiley-VCH, 2014)
This is the follow-up handbook to the bestselling Metal-Catalyzed Cross Coupling Reactions, the definitive reference in the field. In line with the enormous developments in this area, this is not so much a new edition, but rather a new book in three volumes with over 50% more content. This new content includes C-H activation, shifting the focus away from typical cross-coupling reactions, while those topics and chapters found in Diederich/de Meijere's book have been updated and expanded. With its highly experienced editor team and the authors reading like an international Who's-Who in.